Communities of practice with visiting scholars - Magnuson, Paul J.; Hacifazlioglu, Ozge; Carber, Steven; Newman, Rae; Craig, CJ; Mena, J; Kane, RG (Emerald Group Publıshıng Ltd, 2023)
A boarding school research center annually invites students, professors, and others to collaborate with faculty members, forming interconnected communities of practice. The authors interviewed visitors to determine how their experience contributed to their identity as a scholar and the extent to which they felt part of a community of practice. Categorizing emergent themes according to Wenger's (1998) categories of communities of practice, we identified six subthemes that characterize their experience. All participants valued their stay and expressed a desire to remain connected to the school, visiting scholars, and other people they met and now consider part of their network.
Keywords: Communities of practice; visiting scholars; high school; professional development; collaboration; networking